Pengamanan Sertifikat Tanah Digital menggunakan Digital Signature SHA-512 dan RSA - Leonardo Refialy; Eko Sediyono; Adi Setiawan (Maranatha University Press, 2015)
Land trading as investment is sometimes find some barriers or problems. One of the problems is illegal or misclaimed of the land certificate. Badan Pertanahan Nasional (BPN) and Pejabat Pembuat Akta Tanah (PPAT) as institutions and correlated parties in the process of land certificate making need a system to handle the problem of falsification land certificate. The purpose of this research is to make secure system of digital land certificate document with a data protection system to detect if there is a falsification activity from certain party. This research hopefully can help BPN and PPAT as authorized institution of land certificate making and to lower the number of falsification. Digital signature SHA 512 and RSA are used in this research as a solution to keep data integrity of land certificate in a digital format, in this case, in an electronic book with.pdf format. Digital signature derived from xref table in.pdf file. This program has been consulted with BPN and PPAT officer in Salatiga. The result is, this program can be used and applied for authentication process of digital land certificate and help BPN to solve the problem of high number of falsification digital land certificate.Â Keywordsâ€”Sertifikat Tanah Digital, Digital Signature, Hash SHA 512, RSA, Integritas Data, Xref-Table